Factors Related to Delirium of Intensive Care Untints in Korea: A Systematic Review - Nam Young Kim; Se Ang Ryu; Yun Hee Kim (Tehran University of Medical Sciences, 2021)
Background: The delirium in Intensive Care Untints (ICU) patients is a major cause of unplanned extubation, increased length of hospital day. This study aimed to review systematically risk factors associated with the occurrence of delirium among ICU patients in South Korea. Methods: Data collection was done with domestic literature search databases including KMbase, KoreaMed, KISS, and KisTi and also with hand searching, from February 17 to May 19, 2019. Two researchers independently selected research literatures, and three researchers summarized and identified related variables based on data extraction methods. Results: Overall, 140 articles identified, 18 articles met the inclusion criteria for review. According to the results of the methodological quality, one article was found to have a high level of quality, while the remaining 17 articles belonged to the medium level. Those factors found to be highly associated with delirium by more than 9 out of the 18 selected studies were listed as follows; age, the application of ventilator, APACHE II score, comorbidity, the application of restraint, and educational level. In addition, catheter insertion and the application of artificial airway were also found to have significant relevance with the occurrence of delirium. Conclusion: For management of delirium among ICU patients, it is necessary to eliminate and prevent delirium-associated risk factors, and also to detect and treat the delirium early through regular monitoring using an appropriate screening tool for delirium.